Understanding medical destination choice behaviour: an exploratory approach - Putit, Lennora; Ahmad Suki, Amirah; Abdullah, Mohamad Fariz; Suib, Fatin Husna (Universal Publishers - Boca Raton, Florida, USA, 2022)
Over the past decade, medical tourism has been growing progressively in developing countries of Eastern Europe, South Asia, Southeast Asia, and Middle East. This paper aims to conceptually understand medical tourists’ (or consumers) intentional behaviour to destined countries of their choice within the ‘Halal’ (Permissible) medical tourism sector. It specifically attempts to explore factors influencing their intention towards a preferred destination for sourcing shariah compliance based medical care services. Using an in-depth interview technique, a total of 15 qualitative data were collected from targeted respondents involved in medical-care tourism related activities via a digital voice tape recorder; transcribing and coding processes were carried out using ATLAS.TI software. Initial findings have shown several themes that were grounded in the designated semi- structured questions such as attitude, subjective norm, behavioural control, destination image, religiosity, and cost. The results revealed significant suggestions and opinions from the participants on the potential adoption of ‘Halal’ medical destination choice behaviour. Several managerial implications were further discussed.